Productivity, water- and nitrogen-use efficiency, and profitability of pearl millet (Pennisetum glaucum) under different nitrogen applications in semiarid region of Nigeria - Ajeigbe, Hakeem A.; Akinseye, Folorunso M.; Kamara, A.; Tukur, A.; Inuwa, A.H. (Hindawi Limited, 2020)
An experiment was conducted to examine the performance of pearl millet under different nitrogen (N) fertilizer rates in two locations in the semiarid zone of Nigeria. The objective was to evaluate the effects of different N rates on pearl millet yields, water- and nitrogen-use efficiency, and profitability. Grain yield increased by 23, 26, 32, 32, and 27% and by 38, 41, 54, 58, and 56% compared to unfertilized plots when applying 20, 40, 60, 80, and 100 kg Nha−1 in Minjibir and Gambawa, respectively. Similarly, stalk yield increased by 4, 3, 9, 9, and 9% and by 16, 24, 36, 40, and 37% compared to unfertilized plot when applying 20, 40, 60, 80, and 100 kg Nha−1 in Minjibir and Gambawa, respectively. The variations in GY that could be explained by TWU and NUE were 28% and 26% in Minjibir and 46% and 41%, respectively, in Gambawa. There was a strong and positive correlation (R = 0.81 and R = 0.95) between WUE and GY across N-fertilizer rates and pearl millet varieties in both locations. An increase in N-fertilizer levels increased WUE, confirming the optimal application of 60 kg Nha−1 in Minjibir and of 80 kg Nha−1 in Gambawa. Similarly, the highest net economic return (NER) of US$610 ha−1 was obtained at 60 kg Nha−1 in Minjibir and the highest NER of US$223 ha−1 was obtained at an application rate of 80 kg Nha−1 in Gambawa. Break-even yield was above 1000 kg ha−1, signifying that average farmer with a mean yield of less than 1000 kg ha−1 produces millet at a loss.